PEMANFAATAN VIDEO SCRIBE SPARKOL SEBAGAI MEDIA PEMBUATAN TUGAS DAN LATIHAN BAGI SISWA/I SMA 3 MUHAMMADIYAH PADANG - Hesty Aisyah; Elizamiharti; Elisa Daniati Edison; M. Tasnim; Cyntia Lasmi Andesti; Sri Restu Ningsih (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The use of technology on computer devices in the teaching and learning process as a job support plays a very important role in an organization or school. The main function of this technological device is to increase efficiency in learning. Based on the above, Metamedia University lecturers helped find solutions to the above problems by holding community service activities, namely with the theme of using Video Scribe Sparkol as a medium for making assignments and training for SMA 3 Muhammadiyah Padang students. The purpose of this activity is for teachers to be able to make training materials for students, in order to make teaching more interesting, so that students' motivation increases and is able to eliminate boredom and train students' thinking levels from simple thinking to complex thinking. The method used in this training is in the form of lectures, training materials and questions and answers about the use of Scribe Sparkol's video features. The result of this training activity is that it can help students at SMA 3 Muhammadiyah in dealing with increasingly advanced technological developments, especially in maximizing the use of the features contained in the Scribe Sparkol video.